2015
DOI: 10.1111/aos.12519
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic macular ischaemia is associated with narrower retinal arterioles in patients with type 2 diabetes

Abstract: ABSTRACT.Purpose: Diabetic macular ischaemia (DMI) is an important cause of visual loss in patients with diabetes, but its relationship to the larger retinal vessels is unknown. We examined whether retinal vessel calibre is related to DMI. Methods: Clinic-based case-control study of patients with type 2 diabetes. The presence and severity of DMI was assessed using Early Treatment Diabetic Retinopathy Study (ETDRS) protocols from fundus fluorescein angiographic (FFA) images. Custom software was used to quantify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 42 publications
(70 reference statements)
0
21
0
Order By: Relevance
“…[3] This pathological condition is characterized by enlargement of the physiological capillary-free zone located at the center of the macula, also known as the foveal avascular zone (FAZ), along with perifoveal capillary dropout.…”
Section: Introductionmentioning
confidence: 99%
“…[3] This pathological condition is characterized by enlargement of the physiological capillary-free zone located at the center of the macula, also known as the foveal avascular zone (FAZ), along with perifoveal capillary dropout.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, assessment of diseases characterized by ischemia, injury, and inflammation may be substantially enhanced by separating the two types of vessels. [1][2][3][4][5] Automatic separation allows for fast, high-volume analysis that is not user dependent. This will ultimately be included in a total automated procedure that will include detection and segmentation, 7 3-D reconstruction, 6 and analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of the arteriolar and venular content, wall structure, and network organization is thus essential to our understanding of multiple disease scenarios. For example, in the eye, narrowing of retinal arterioles is related to diabetic macular ischemia, 1 and the arteriole-to-venule ratio is associated with hypertensive retinopathy. 2 In the brain, proper arteriolar function is essential to maintaining adequate cerebral blood flow; occlusion of even a single penetrating arteriole connecting the pial network to the subsurface network results in the death of a 0.5-mm cylinder of cortical tissue.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we did not find a statistically significant change in central retinal arteriolar or venular diameter. Liew et al (2015) elegantly demonstrated an inverse association between DMI severity and central retinal arteriolar diameter, but this was no longer statistically significant when patients who had panretinal photocoagulation (PRP) were excluded. Panretinal photocoagulation is considered an important confounder because it has been demonstrated that patients who had PRP were more likely to have central retinal arteriolar narrowing (Grauslund et al 2009).…”
Section: Referencementioning
confidence: 99%
“…On the contrary, we gave input to the authors prior to publication, which was consistent with the comments above and cautioned against drawing any valid conclusions from this particular study design. read with great interest the article 'Diabetic macular ischaemia is associated with narrower retinal arterioles in patients with type 2 diabetes' by Liew et al (2015). The authors should be congratulated on this important article regarding diabetic macular ischaemia (DMI) which is a severe vision-threatening condition, even in the anti-VEGF era.…”
mentioning
confidence: 99%